2009
DOI: 10.1007/s00595-008-3937-x
|View full text |Cite
|
Sign up to set email alerts
|

A foreign body granuloma after gastric perforation mimicking peritoneal dissemination of gastric cancer: Report of a case

Abstract: This report presents the case of a 58-year-old man who was found to have foreign body granulomas (FBGs) that mimicked disseminated gastric cancer. The patient presented with a severe attack of acute upper abdominal pain, was admitted to the hospital, and thereafter underwent an immediate laparotomy due to a diagnosis of an upper gastrointestinal perforation. Follow-up endoscopy revealed an ulcer scar measuring 2 cm in size in the anterior wall of the middle stomach. The pathological examination of biopsy speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…[7][8][9] The search of the English literature revealed a case report on foreign body granuloma in peritoneum mimicking disseminated gastric cancer. [10] Granuloma of the peritoneum induced by activated charcoal from intraperitoneal chemotherapy in a patient with gastric ulcer, which mimicked peritoneal metastasis, has also been reported. [11] Food starch granuloma of the appendix and peritoneum after perforation of gastric ulcer has also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The search of the English literature revealed a case report on foreign body granuloma in peritoneum mimicking disseminated gastric cancer. [10] Granuloma of the peritoneum induced by activated charcoal from intraperitoneal chemotherapy in a patient with gastric ulcer, which mimicked peritoneal metastasis, has also been reported. [11] Food starch granuloma of the appendix and peritoneum after perforation of gastric ulcer has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] Most of the case reports show that the granulomas of the stomach were diagnosed after gastric resection procedures. [10,18] A few other reports have suggested causal role of H. pylori infection in the pathogenesis of granulomas. [19]…”
Section: Discussionmentioning
confidence: 99%
“…IFBGs associated with lycopodium, talcum, and starch powders from surgical gloves have previously been reported, and these IFBGs can be quite difficult to differentiate from cancerous nodules[ 7 , 9 , 10 ]. Akita et al [ 5 ] reported that food starch released from gastrointestinal perforations could cause multiple IFBGs, mimicking peritoneal dissemination; they reported a case in which tenderness and guarding over the entire abdomen was observed due to a gastric cancer perforation, which was treated surgically. Two months later, many small, white granulomas mimicking peritoneal dissemination were observed, particularly in the upper abdominal cavity, which were diagnosed as IFBGs based on frozen sections during the second operation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in rare cases, bowel perforation, bile or gallstone spillage, and foreign bodies unrelated to operations, such as fish bones, can result in IFBGs[ 4 - 6 ]. Furthermore, IFBGs sometimes occur multifocally and can closely resemble peritoneal dissemination, leading to misdiagnosis[ 5 , 7 ]. Here, we present a case of IFBGs mimicking peritoneal dissemination 4 mo after an operation to treat an incarcerated and perforated femoral hernia.…”
Section: Introductionmentioning
confidence: 99%
“…As pancreatoduodenectomy is a major undertaking fraught with major complications, we feel it is unfortunate that our patient underwent this procedure because of a mass that was later discovered to be due to FBGCR. However, FBGCR has been reported to be the cause of formation of masses that were mistaken for malignant deposits [7-10]. These masses have even led to surgical resection of the suspected areas [8,10].…”
Section: Discussionmentioning
confidence: 99%